The Epigenetic Reprogramming Roadmap in Generation of iPSCs from Somatic Cells. Issue 12 (20th December 2015) - Brix, Jacob; Zhou, Yan; Luo, Yonglun
Abstract: Reprogramming of somatic cells to induced pluripotent stem cells (iPSCs) is a comprehensive epigenetic process involving genome-wide modifications of histones and DNA methylation. This process is often incomplete, which subsequently affects iPSC reprograming, pluripotency, and differentiation capacity. Here, we review the epigenetic changes with a focus on histone modification (methylation and acetylation) and DNA modification (methylation) during iPSC induction. We look at changes in specific epigenetic signatures, aberrations and epigenetic memory during reprogramming and small molecules influencing the epigenetic reprogramming of somatic cells. Finally, we discuss how to improve iPSC generation and pluripotency through epigenetic manipulations.